HUBUNGAN KEKUATAN OTOT LENGAN DAN KEKUATAN OTOT PERUT DENGAN KETEPATAN FLYING SHOOT BOLA TANGAN - Koswara, Edi; Anang Setiawan; Nur Mahfuzah Agustin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine whether there is a relationship between arm muscle strength and abdominal muscle strength together with the accuracy of handball flying shoots. The research method used in this study is a correlational method with a quantitative approach. The population in this study was the Male Athletes of the Handball Team of Cirebon Regency XIV West Java Provincial Sports Week which amounted to 12 people with a sampling technique using the total sample technique "saturated sampling".The instruments in this study are 1) push ups; 2) sit ups; 3) flying shoot; The data analysis technique uses multiple regression tests. The results of this study show that there is a relationship between arm muscle strength and abdominal muscle strength together with the accuracy of handball flying shots in Handball Men's Athletes Cirebon Regency West Java Handball Provincial Sports Week XIV